Design, analysis and prototyping of active tab rotor - Kobiki, N.; Tanabe, Y.; Aoyama, T.; Kim, D.-H.; Kang, H.J.; Wie, S.-Y.; Kim, S.-H. (My University, 2015)
JAXA (Japan Aerospace Exploration Agency) and KARI (Korea Aerospace Research Institute) jointly started the activities related to the research and development of Active Tab as the helicopter noise reduction technique. KARI constructed the analytical methodology consisting of the aerodynamic, structural dynamic and acoustic codes for defining the requirements for and evaluation of the performances of Active Tab installed in a Mach scaled assumed blade. Based on the defined requirements, JAXA carried out the conceptual design study, developed and evaluated the performances of the Active Tab drive mechanism. The analytical results show Active Tab satisfying the requirements has the sufficient noise reduction capability. The evaluation for the Active Tab drive mechanism demonstrated the dynamic performance and durability available for the practical use installed in helicopter blades.
Keywords: Acoustics